The Oxford handbook of international political theory - Brown, Chris 1945-; Eckersley, Robyn 1958- (The Oxford handbooks of international relations, 2018)
International Political Theory (IPT) focuses on the point where two fields of study meet - International Relations and Political Theory. It takes from the former a central concern with the 'international' broadly defined; from the latter it takes a broadly normative identity. IPT studies the 'ought' questions that have been ignored or side-lined by the modern study of International Relations and the 'international' dimension that Political Theory has in the past neglected. A central proposition of IPT is that the 'domestic' and the 'international' cannot be treated as self-contained spheres, although this does not preclude states and the states-system from being regarded by some practitioners of IPT as central points of reference.00This Handbook provides an authoritative account of the issues, debates, and perspectives in the field, guided by two basic questions concerning its purposes and methods of inquiry. First, how does IPT connect with real world politics? In particular, how does it engage with real world problems, and position itself in relation to the practices of real world politics? And second, following on from this, what is the relationship between IPT and empirical research in international relations? This Handbook showcases the distinctive and valuable contribution of normative inquiry not just for its own sake but also in addressing real world problems.